Stability and Thermal Conductivity Evaluation of Less Concentration Surfactant Wrapped Functionalized Graphene Dispersed in Ethylene Glycol - Bakthavatchalam, B. (Springer Science and Business Media Deutschland GmbH, 2021)
Graphene, a single-layer hexagonal carbon atom lattice, has recently emerged as an intriguing framework for basic experiments of condensed matter physics, as well as an exciting candidate for potential usage of heat transfer systems. Moreover, graphene nanofluid has excellent anisotropic behavior regarding thermal conductivity. The most critical concerns for usage in diverse graphene nanofluid applications are inadequate dispersibility and insufficient stability in solvents. This study explores the stability and thermal conductivity of functionalized graphene wrapped with octadecylamine (ODA) surfactant and sonicated in ethylene glycol base fluid. In this study, graphene nanoparticles are functionalized with chemicals like nitric acid and sulphuric acid, and it is wrapped with ODA, and its thermal conductivity and dispersion behavior is evaluated. The results show that the maximum thermal conductivity was 0.43Â W/m.K at 55Â Â°C while the formulated nanofluid is stable for six days. Â© 2021, The Author(s), under exclusive license to Springer Nature Singapore Pte Ltd.